Prevalence and associated factors of postpartum depression among immigrant women in Guangzhou, China - Ribo Xiong; Aiwen Deng (BMC, 2020)
Abstract Background Although there has been mounting research on postpartum depression (PPD), the impact of immigration on PPD has remained quite unexplored. The purpose of this study is to investigate the prevalence and associated factors of PPD among immigrant women living in Guangzhou at 6 weeks postpartum. Methods A cross-sectional study was conducted involving 1230 immigrant women in a tertiary hospital of Guangzhou from December 2016 to December 2017 at 6 weeks postpartum. The Chinese version of Edinburgh Postnatal Depression Scale and a structured questionnaire regarding associated factors were administered to all participants. Multivariate logistic regression was used to determine factors that were significantly associated with PPD. Results The prevalence of PPD among immigrant women at 6 weeks postpartum was 34.0%. A multivariate logistic regression model identified significant obstetric and social factors as: living in Guangzhou for less than 2 years, insufficient family income, poor social support and marital relationship. Conclusion Prevalence of PPD among immigrant women from Guangzhou at 6 weeks postpartum is high. The development of PPD among immigrant women is associated with individual and social factors. There's an urgent need for healthcare providers to take a more active role in engaging immigrant women in their psychological needs.